Mobility, participation and sustainable regeneration. Urban projects in Liguria Region - Spadaro, Ilenia; Pirlone, Francesca (TeMA - Journal of Land Use, Mobility and Environment, 2024)
The paper reports different experiences in which mobility, participation and sustainable regeneration represent fundamental issues for our cities. The applications are developed in idea competitions promoted by municipal governments and associations. Rethinking mobility and orienting actions towards sustainability means putting people at the center of urban strategies. In this context, the 4 innovation helix framework, and so, the involvement of local actors: people, university, company and administration, is indispensable for guiding society towards sustainable development according to 2030 Agenda. In the experiences illustrated, the role of the University emerged as a connector capable of collaborating together and building synergies between the various actors involved with the common objective of improving the liveability of our cities. Liveability which is closely linked to the improvement of mobility services and their intramodality with important repercussions on the accessibility of services. The actions undertaken for more sustainable mobility lead to a path that increases the demand for integrated services for the movement of people and goods but also the attractiveness of the area from an environmental, social, tourist and economic point of view. The urban projects presented were carried out as part of university courses in collaboration with public administrations of the Ligurian Region.